Adaptación de las Sub pruebas que miden la dimensión conciencia fonológica de la batería de iniciación de la lectura (BIL 3-6) - Mufarech Rey, Cristina (2021)
Phonological awareness is the set of skills of the student to identify and make use of the different elements that constitute oral language, that is, words, syllables and phonemes. It is an essential element for the acquisition of reading, because it not only allows the child to understand the relationships between the written text and their own language, but also facilitates the decoding process so difficult in its beginnings. The objective of the present work consisted in the adaptation of the sub tests that measure the phonological awareness dimension of the Reading Initiation Battery (BIL 3-6) in the local context. The test was applied to 100 children aged 4 and 5 from private pre-schools in Metropolitan Lima. The choice of the sample was carried out randomly. In the first place, evidence of validity, related to the content of the test was found through the method of expert judges. finding an Aiken V coefficient higher than .83 for all items. Then, an attempt was made to obtain validity evidences based on the internal structure, which could not be carried out due to the sample size. Finally, the reliability of the scores was estimated by the internal consistency method with the Omega coefficient, finding that one of the areas presents a value greater than .70, which is considered an acceptable value of reliability, but the other 4 areas are not considered acceptable, since all their values are less than .70 (Campo-Arias & Oviedo, 2008).